Differences from K-13 Curriculum to Independent Curriculum Based on Teacher Perceptions - Saputri, Desi Helen; Azzahra, Diva Anisa; Sari, Dwi Vita; Wulan, Elita Nur; Putri, Sifa Apriliya (Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The purpose of this study is to explore how teachers perceive the transition from a K-13 curriculum to an independent curriculum. The method used is a descriptive research type qualitative approach. Both students and students' parents and her 4th grade teacher in SD Negri 1 Ganjaran. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The researchers found that teachers' opinions on the 2013 curriculum changes in SD Negri 1 Ganjaran varied widely. Many teachers rated the changes from the 2013 curriculum to their own curriculum as very positive and made it easier to meet learning objectives. However, no matter how strong the idea of curriculum change is, implementation will be difficult if teachers are not adaptable or prepared. As educators, effective implementation of the curriculum within an educational institution is essential to successfully achieving educational goals.